Value Chain Analysis of Climate-smart Shan Tea Production in the Northern Mountainous Region of Vietnam - Tran, Tuong; Branca, Giacomo; Arslan, Aslihan; Van Mai, Trinh (Italian Review of Agricultural Economics, 2016)
Agricultural production in the face of climate change requires a transformation and reorientation in agricultural systems and policy making. Climate-smart agriculture (CSA) is such a transformative approach that aims to sustainably increase food security, by improving adaptation to climate change and capturing potential mitigation co-benefits. CSA approach goes beyond field level practices and encompasses value chains, food systems as well as enabling environments and policy. This paper provides a site-specific analysis of the contributions of organic and conventional Shan tea value chains (VCs) to CSA objectives by using a interdisciplinary approach. Our findings show that both organic and conventional Shan tea VCs simultaneously contribute to food security and adaptation. Shan tea plays a vital role in securing household income and has a strong potential in helping households to coping with extreme weather events. Potential mitigation options are mainly in the processing stage (GHG emissions from coal burning).